The Impact of Leadership and Work Environment on Employee Performance at Aloft Bali Seminyak Hotel : Pengaruh Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Karyawan Hotel Aloft Bali Seminyak - Permatasari, Nindy; Sihombing, Irene Hanna H.; Adinda, Clearesta (Institut Pariwisata dan Bisnis Internasional, 2024)
This study examines the impact of leadership style and work environment on employee performance at the Aloft Bali Seminyak Hotel. Employee performance plays a crucial role in the success of any company, particularly in the hospitality industry, where service quality directly affects customer satisfaction and business outcomes. A good leadership style and a positive work environment can significantly enhance employee performance, while poor leadership and work conditions can detract from it. The study utilized a quantitative approach, collecting data from 42 respondents through questionnaires using a 5-point Likert scale to assess 49 statement items. The data were analyzed using multiple linear regression, t-test, f-test, and the coefficient of determination, processed with SPSS version 26 for Windows. The results show that leadership style and work environment together explain 61% of the variance in employee performance, with the remaining 39% influenced by factors not explored in this study. The findings reveal that both leadership and work environment have a significant positive effect on employee performance. Effective leadership, characterized by support, motivation, and clear communication, boosts job satisfaction and productivity. Similarly, a conducive work environment, including appropriate work conditions and teamwork, contributes to enhanced employee engagement and performance. This study highlights the importance of leadership style and a supportive work environment in driving employee performance in the hospitality sector. It suggests that hotel management should prioritize leadership development and create a positive work environment to improve employee outcomes, which in turn can enhance the overall success of the organization.